Rekonstruksi Tawassul Ghairu Masyru’ Perspektif Salafiyah Wahabiyah (Studi Analisis Kritis Kajian Ushul) - Agustang; Andi Muh Ishak; Faza Achsan Baihaqi (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
This Research aim to analyze and critcisis masyru' from the perspective of Salafiyah Wahabiyah. The purpose of this study is to analyse the concept of tawassul Salafiyah Wahabiyah, criticise their istinbat method on tawassul ghairu masyru', and reconstruct this type of tawassul. This research is a qualitative library research. This research uses the ushul normative approach. The results of the research are as follows: First, the concept of tawassul from the perspective of Salafiyah Wahabiyah is divided into two, namely tawassul masyru' (permissible) and tawassul ghairu masyru' (not permissible) whose law is haram. Secondly, Salafiyah Wahabiyah is in the error of istinbath on tawassul ghairu masyru'. Third, the reconstruction process has straightened out the error of Salafiyah Wahabiyah's istinbat by placing tawassul ghairu masyru' in the realm of fiqh and turning it into tawassul masyru', whose law is permissible, even musthab to the great Prophet Muhammad Saw. Based on the results of the research, the religious thought of Salafiyah Wahabiyah on the problem of tawassul ghairu masyru' cannot be used as a reference for Muslims.